Deteccion y Caracterizacion mediante microscopia electronica de diferentes Rhabdovirus vegetales - Lopez Abella, D.=700 1 Diaz Mugica, M.V.; Diaz Ruiz, J.R.; Moreno, R.; Rubio Huertos, M.
(Es, En)
ilus., 15 ref.
Keywords: RHABDOVIRUS DE LAS PLANTAS; MICROSCOPIA; TOMATE; COLIFLOR; ESPAÑA; EVONYMUS